An experience of embolization of multiple recurrence pheochromocytoma nodules - Chong, Eng Ngen; Zulkifli, Zuria Amaleen; Abdul Rahim, Ridzuan; Abdul Rahim, Ezamin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Recurrence of pheochromocytoma is quite common. We present a case report of a malignant pheochromocytoma with recurrent nodules in right paranephric and posterior-lateral abdominal wall, which underwent transarterial embolization of the nodules.